CRITICAL ANALYSIS ON THE BENEFITS AND CHALLENGES OF HIGHER EDUCATION INTERNATIONALISATION: CASE OF CHINA - Kabeera, Pontian (The Modern Higher Education Review, 2020)
Internationalization of higher education remains the main module through which knowledge can be bought, sold or even shared among Universities from different countries across the world. It was formerly considered as an ambition through which quality education can be achieved, however it has of recent times changed and became the means through which this mantra of quality education and professional mobility can be effectively attained. The knowledge acquisition and transformation, resource mobilization, talent mobilization especially global research as well as curriculum enactment with the international content are considered to be the primary benefits of internationalization of higher education. As much as internationalization hold countless constructive and positive meanings to the performance of higher education and eventually competent human resource development, there are significant challenges that are associated with this multifaceted and growing phenomenon, which among them includes commercial profit, academic colonization and difficulty in ensuring quality education. The reviews show that through higher education internationalization, significant progress can be achieved since the international exposure can influence policies in higher education, which can bring about considerable changes in the entire education system and education institutions across the world. This paper used Chinese higher education to examine the challenges and the potential of benefits of internationalization of higher education. It implies reviews of articles with respect to internationalization of higher education in the context of china as the papers methodology. Based on this review the paper ascertained several benefits of higher education internationalization in China which include quality human resources, skills development and exposure, professional mobility and research development, it also highlighted potential challenges which included academic colonization, low quality education standards and brain drain hence the paper recommends that, there should a proper system for evaluating students who go to study abroad and proper structure of tuition payment.